EFICACIA DEL PROCESO DE ESTERILIZACION DE CICLO FLASH EN AUTOCLAVE DEL INSTRUMENTAL BIOMEDICO - Novoa Paredes, Cecilia Bethsabé del Pilar (2017)
OBJETIVE: ESTABLISHING THE EFFECTIVENESS OF THE FLASH CYCLE STERILIZATION PROCESS IN AUTOCLAVE OF BIOMEDICAL EQUIPMENT. MATERIAL AND METHODS: WE PERFORMED A SYSTEMATIC REVIEW, WHICH SYSTHESIZES THE RESULTS OF MULTIPLE PRIMARY INVESTIGATIONS. THE ARE AN ESSETIAL PART OF EVIDENCE-BASED NURSING FOR ITS RIGOROUS METHODOLY, IDENTIFYING RELEVANT STUDIES TO ANSWER QUESTIONS SPECIFIC TO CLINICAL PRACTICE. RESULTS: THE REVIEW OF ARTICLES CORRESPOND TO PUDMED, MEDLINE AND LILACS DATABASES. THE 05 SCIENTIFIC ARTICLES SYSTEMATICALLY REVIEW THE EFFECTIVENESS OF THE SHORT CYCLE STERILIZATION PROCESS IN BIOMEDICAL EQUIPMENT, 20% (01) CORRESPOND TO SPAIN AND 80% TO THE UNITED STATES, ALL OF THEM FRAMED IN THE 05 RESECH ARTICLES. CONCLUSIONS: THE STERILIZATION PROCESS OF SHORT CYCLE IN AUTOCLAVE ACCORDING TO THE STUDIES SHOULD BE LIMITED IN CASE OF EMERGENCY THA THE MANUFACTURER AND TAKING INTO ACCOUND THE 3 CRITICAL STEPS: CLEANING AND DECONTAMINATION, STERILIZATION AND ASEPTIC TRANSFER TO ENSURE STERILIZATION.